Support of Family Member, Public Figure, and Health Attendant to PSN Behavior and Related Factors - Rangga, Rouhdy; Giang, Nguyen Tra; Azinar, Muhammad (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
The eradication of mosquito’s breeding place (PSN) is the most effective efforts to prevent the increasing prevalence of DHF in Demak which is 43% of its area is endemic. This study aims to determine the factors related to PSN behavior by family members.This is an observational analytic study with cross sectional approach using 210 samples divided into 3 groups of respondents (father, mother, child) with purposive sampling technique. Data were obtained through questionnaire based on interview results and analyzed by chi square. The results of the research on the father respondents showed that there was a relationship between the support of family members (p=0.001), support of community leaders (p=0.007), and support of health attentand (p=0.005) with PSN behavior. In mother respondents was found that the support of family members (p=0.006) and support of health officer (p=0.009) correlated with PSN behavior. In the child respondents was found that the support of family members (p=0.000), support of community leaders (p=0.007), and support of health officer (p=0.009) correlated with PSN behavior. It was concluded that the support of family members and support of health attendant was related to the behavior of PSN in all groups of respondents, and support of community leaders related to PSN behavior to the respondents of father and child.